Exploring Chronic Congenital Heart Disease Using Interpretative Phenomenological Analysis (IPA): A Methodological Insight - Kristy Waller; Gina Clarkson (International Journal of Qualitative Methods)
This paper presents a methodological insight in using the Interpretative Phenomenological Analysis (IPA) method in a study of young adults with chronic congenital heart disease (ACHD). It is not well understood how young adults with CHD make sense of their lives beyond the existing quality of life measures. Exploring this research topic guided by the three principles of IPA: (a) phenomenology, (b) hermeneutics, and (c) idiography, we found our study elucidated one’s sense making growing up with a pediatric chronicity; particularly the role of researcher ‘as instrument’ for its centrality as an authentic representation of the lived ‘CHD’ experience unfolded. Decisions relevant to data collection and the analytical phase of the research are presented. Insight further involves discussing methodological integrity and the ethical considerations associated with implementing IPA as the foundational framework. We believe using IPA in a cohort of adult congenital heart disease patients provided an in-depth exploration into the meaningfulness of these individuals’ lives. Our study highlights the value of using hermeneutics to advance the growing body of ACHD evidence and other disease-related research studies. Moreover, using the IPA approach contributes to methodological development by promoting interdisciplinary scholarship that disseminates practical, real-world knowledge.